Financial transaction tax, liquidity, and informational efficiency: Evidence from Italy - Valentina Galvani; Matthew Ackman (Heliyon, 2021)
This study investigates whether the liquidity of medium-sized and large caps has been differently affected by the Italian Financial Transaction Tax, among the firms subject to the tax. We evaluate changes in mean and median bid-ask spreads and Amihud (2002) liquidity for aggregate market indexes and at the firm level. After the implementation of the tax, spreads have widened more for medium- than for large-caps, whereas the Amihud liquidity measure remained unaltered for the vast majority of the firms.